2016
DOI: 10.1590/0037-8682-0078-2016
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of hypertriglyceridemia in a Brazilian cohort of people living with HIV/AIDS undergoing antiretroviral treatment in Belo Horizonte, 2001-2010

Abstract: Introduction: Hypertriglyceridemia incidence should be estimated in HIV-infected patients after antiretroviral therapy (ART) initiation. Methods: We retrospectively analyzed clinical data of HIV-infected adults at 3 public referral centers. Cumulative and person-time incidences were estimated for patients without hypertriglyceridemia. Survival time and hazard ratio (HR) were estimated by Kaplan-Meier analysis and Cox proportional regression, respectively. Results: Cumulative and person-time incidences were 40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
1
Order By: Relevance
“…Here, our study paralleled these previous studies, demonstrating that the hyperlipidemia group had a higher level of ART usage. In addition, a meta-analysis of previous studies and our study showed that patients with ART use had a higher hyperlipidemia risk than patients who were not using ART ( Supplementary Table 3 and Supplementary Figures 1–2 ) [ 28 , 29 ]. Our results also suggest that HIV patients may have a higher hyperlipidemia risk when they receive ART regimens in dose- and adherence- dependent manners, especially in the cases of PI, NRTI, and NNRTI regimens.…”
Section: Discussionmentioning
confidence: 62%
“…Here, our study paralleled these previous studies, demonstrating that the hyperlipidemia group had a higher level of ART usage. In addition, a meta-analysis of previous studies and our study showed that patients with ART use had a higher hyperlipidemia risk than patients who were not using ART ( Supplementary Table 3 and Supplementary Figures 1–2 ) [ 28 , 29 ]. Our results also suggest that HIV patients may have a higher hyperlipidemia risk when they receive ART regimens in dose- and adherence- dependent manners, especially in the cases of PI, NRTI, and NNRTI regimens.…”
Section: Discussionmentioning
confidence: 62%
“…Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is associated with opportunistic pathologies due to low activity of the immune system ( Raso et al, 2007 ). Highly active antiretroviral therapy (HAART) is widely recommended for patients with HIV/AIDS as a way to prevent the onset of these pathologies ( Chow et al, 2017 ; Mendicino et al, 2016 ). However, HAART increases the cardiovascular risk of the patients ( Hsue et al, 2009 ; Lipshultz et al, 2003 ; Zareba et al, 2005 ), especially women ( Muyanja et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, protease inhibitors, nucleoside reverse-transcriptase inhibitors (NRTIs), and non-NRTIs (NNRTIs) all increase triglyceride levels and newer drugs have more favorable effects compared to older ones [ 1 , 2 ]. In addition, studies found that the prevalence of hypertriglyceridemia was higher in males with HIV [ 7 , 8 ]. A recent study showed that hypertriglyceridemia is associated with subclinical atherosclerosis and vascular inflammation even in participants with normal low-density lipoprotein cholesterol levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%